Dynamics of fine root carbon in Amazonian tropical ecosystems and the contribution of roots to soil respiration - Trumbore, Susan; Costa, Enir Salazar Da; Nepstad, Daniel C; Barbosa De Camargo, Plínio; Martinelli, Luiz A; Ray, David; Restom, Teresa; Silver, Whendee (Global change biology, 2006)
Radiocarbon (¹⁴C) provides a measure of the mean age of carbon (C) in roots, or the time elapsed since the C making up root tissues was fixed from the atmosphere. Radiocarbon signatures of live and dead fine (<2 mm diameter) roots in two mature Amazon tropical forests are consistent with average ages of 4-11 years (ranging from <1 to >40 years). Measurements of ¹⁴C in the structural tissues of roots known to have grown during 2002 demonstrate that new roots are constructed from recent (<2-year-old) photosynthetic products. High [Delta]¹⁴C values in live roots most likely indicate the mean lifetime of the root rather than the isotopic signature of inherited C or C taken up from the soil. Estimates of the mean residence time of C in forest fine roots (inventory divided by loss rate) are substantially shorter (1-3 years) than the age of standing fine root C stocks obtained from radiocarbon (4-11 years). By assuming positively skewed distributions for root ages, we can effectively decouple the mean age of C in live fine roots (measured using ¹⁴C) from the rate of C flow through the live root pool, and resolve these apparently disparate estimates of root C dynamics. Explaining the ¹⁴C values in soil pore space CO₂, in addition, requires that a portion of the decomposing roots be cycled through soil organic matter pools with decadal turnover time.